Exercise dose and diabetes risk in overweight and obese children: A randomized, controlled trial - Davis, Catherine L (2012)
CONTEXT: Pediatric studies showed that aerobic exercise reduces metabolic risk, but dose response information is not available. OBJECTIVE: Test the effect of aerobic training dose on insulin resistance, fatness, visceral fat, and fitness in overweight, sedentary children, and test moderation by sex and race. DESIGN, SETTING, AND PARTICIPANTS: Randomized, controlled, efficacy trial from 2003 through 2007, in which 222 overweight or obese, sedentary children (mean age, 9.4 yrs; 42% male, 58% black) were recruited from 15 public schools in the Augusta, GA area. INTERVENTION: Low-dose (20 min/d, n = 71) or high-dose (40 min/d, n = 73) aerobic training (13 ± 1.6 wk, 5 d/wk), or control condition (usual physical activity, n = 78); 94% retention. MAIN OUTCOME MEASURES: Prespecified primary outcomes were type 2 diabetes risk at posttest, assessed by insulin area under the curve (AUC) from oral glucose tolerance test, aerobic fitness, percent body fat via dual-energy x-ray absorptiometry, and visceral fat via magnetic resonance, analyzed by intent-to-treat. RESULTS: Most children (85%) were obese. At baseline, the mean BMI was 26 (SD = 4.4). Reductions in insulin AUC were larger in the high-dose (adjusted mean difference [95% CI], −3.56 [−6.26 to −0.85], P = .01) than low-dose group (−2.96 [−5.69 to −0.22], P = .03) ×10(3) μU/mL) vs control group. Dose-response trends were also observed for body fat (−1.4 [−2.2 to −0.7], P < .001; −0.8 [−1.6 to −0.07] %, P =.03) and visceral fat (−3.9 [−6.0 to −1.7], P < .001; −2.8 [−4.9 to −0.6] cm(3), P = .01) in the high- and low-dose vs control groups, respectively. Effects in the high- and low-dose groups vs control were similar for fitness (2.4 [0.4 to 4.5], P =.02; 2.4 [0.3 to 4.5] mL/kg/min, P = .03). High- vs. low-dose group effects were similar for these outcomes. There was no moderation by sex or race. CONCLUSIONS: Three months of 20 or 40 min/d aerobic training improved fitness, and demonstrated dose-response benefits on insulin resistance, general and visceral adiposity in sedentary, overweight or obese children, regardless of sex or race. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT00108901